Konseling Sebaya: Kesehatan Mental Dan Well-Being Anggota Forum Desa Inklusi - Mumpuni, Sesya Dias; Florina, Ike Desi; Nurhayati, Sri Adi; Nurpratiwiningsih, Laelia; Putro, Hijrah Eko; Susilowati, Novi; Mubarokah, Nada Adhani; Istiqomah, Nur; Septiana, Wiwit Cahya; Adinda, Choirunnisa; Lestari, Fiqih Indah Yuni; Chiisai, Ayu Putri; Putri, Novi Mardiani; Rini, Eka Febry Setia; Ambarwati, Rani Tri (Jurnal Bimbingan dan Konseling Pandohop, 2024)
A person's readiness to engage in peer counseling is strongly influenced by mental health and well-being. Peer counseling conducted by people with disabilities will greatly affect the self-esteem of people with disabilities in the community. This research method uses quantitative with 40 respondents who filled out a mental health and well-being questionnaire. The selection of respondents used non-probability sampling techniques. The result of this study is an index analysis consisting of the respondent's mental health index value of 79.25 categorized as Good and the index value of the well-being indicator of 71.93 categorized as Good. The researcher concluded that peer counseling needs to be prepared for mental health and well-being. Mental health consists of 4 indicators including depression or anxiety, dementia, mental (psychiatric) or behavioral disorders, and sleep problems. On well-being consists of 24 indicators including assessing the quality of life, assessing overall health, ability to do activities, satisfied with oneself, satisfied with a relationship, living conditions, having enough energy, having enough money to meet needs, perceived loneliness, feeling a lack of friendship, feeling abandoned, feeling isolated from others, yesterday feeling happy, yesterday feeling enthusiastic, yesterday feeling satisfied, yesterday feeling angry, yesterday feeling frustrated, yesterday feeling tired, yesterday feeling sad, yesterday feeling stressed, yesterday feeling lonely, yesterday feeling happy, yesterday feeling enthusiastic, yesterday feeling satisfied, yesterday feeling angry, yesterday feeling frustrated.